Albright hereditary osteodystrophy: dental management case report - Stephanie Anagnostopoulos FRIEDRICH; Jonas RODRIGUES; Berenice Barbachan e SILVA (Faculdade São Leopoldo Mandic, 2018)
Albright hereditary osteodystrophy is a disorder comprising phenotypic characteristics of genetic origin, such as short stature, obesity, and brachydactyly. It is a rare disorder and is related to pseudohypoparathyroidism. Within dentistry, it may be associated with enamel hypoplasia and late eruption. Furthermore, due to neurological problems, these patients may impose behavioural difficulties during dental appointments. The present study aims to describe the case of a patient with a possible diagnosis of Albright hereditary osteodystrophy, presenting symptoms and limitations to dental management.